UPAYA PENYELESAIAN KONFLIK KEPULAUAN NATUNA DALAM TINJAUAN HUKUM INTERNASIONAL (Kasus Sengketa Indonesia dengan China) - Ni Luh Putu Marta Puspita Yanti (Jurnal Ilmu Hukum Sui Generis, 2022)
The purpose of this article is to find out how to resolve the Natuna Islands dispute between Indonesia and China in a review of international law. Indonesia is a country consisting of thousands of islands so it is known as a maritime country. So it cannot be ruled out if Indonesia is involved in a dispute because Indonesia has a lot of abundant natural resources in its territory. One of Indonesia's disputes with other countries, namely China, is the dispute over the Natuna Islands. So in the Natuna Islands dispute, it has several impacts, including the unstable economy, causing world divisions, harming the country in terms of politics, and causing problems in social life. Regarding this impact, of course, efforts are needed to resolve disputes. The resolution of the dispute over the Natuna Islands is to improve the management of the territorial borders of the Natuna Islands, to increase economic activities through oil exploration in the Natuna Islands region. As well as dispute resolution in international law reviews.